Enhanced limonene production in a fast-growing cyanobacterium through combinatorial metabolic engineering - Po-Cheng Lin; Fuzhong Zhang; Himadri B. Pakrasi (2021)
Terpenoids are a large and diverse group of natural products with commercial applications. Microbial production of terpenes is considered as a feasible approach for the stable supply of these complex hydrocarbons. Cyanobacteria, photosynthetic prokaryotes, are attractive hosts for sustainable bioproduction, because these autotrophs require only light and CO2 for growth. Despite cyanobacteria having been engineered to produce a variety of compounds, their productivities of terpenes are generally low. Further research is needed to determine the bottleneck reactions for enhancing terpene production in cyanobacteria. In this study, we engineered the fast-growing cyanobacterium Synechococcus elongatus UTEX 2973 to produce a commercially-used terpenoid, limonene. We identified a beneficial mutation in the gene encoding geranylgeranyl pyrophosphate synthase crtE, leading to a 2.5-fold increase in limonene production. The engineered strain produced 16.4 ​mg ​L−1 of limonene at a rate of 8.2 ​mg ​L−1 day−1, which is 8-fold higher than limonene productivities previously reported in other cyanobacterial species. Furthermore, we employed a combinatorial metabolic engineering approach to optimize genes involved in the upstream pathway of limonene biosynthesis. By modulating the expression of genes encoding the enzymes in the MEP pathway and the geranyl pyrophosphate synthase, we showed that optimization of the expression level is critical to enhance limonene production in cyanobacteria.